Active Surveillance in Prostate Cancer: Can We Expand the Indications? - TİNAY, İLKER (GALENOS YAYINCILIK, 2016)
Common usage of prostate-specific antigen screening and prostate biopsies increases diagnosis rate of clinically insignificant prostate cancer. Nowadays, active surveillance is an alternative approach for overtreatment of patients diagnosed with low-risk, localized prostate cancer. Although there is no consensus on ideal active surveillance protocol for patient-inclusion and follow-up, it was reported that protocols that are in use and accepted by various centers are as successful as curative radical therapies concerning survival of cancer. New screening methods for diagnoses of prostate cancer, the follow-up and studies on bio-/genomic markers are promising. These positive developments bring one question on mind: Can we expand the indications for active surveillance in prostate cancer?
Keywords: Active surveillance; prostate cancer; prostate-specific antigen; MORTALITY; RADIATION; BIOPSY; IMPACT